Basic researchEfficacy of Setarud (IMODTM), a novel electromagnetically-treated multi-herbal compound, in mouse immunogenic type-1 diabetes - Mohseni-Salehi-Monfared, Seyed Sajad; Habibollahzadeh, Ebad; Sadeghi, Hooman; Baeeri, Maryam; Abdollahi, Mohammad (Archives of Medical Science, 2010)
Introduction : The aim of this study was to evaluate the effects and mechanisms of Setarud (IMODTM) as a multi-herbal medicinal formula on a mouse model of type 1 diabetes. Material and methods : Autoimmune diabetes was induced by multiple low-dose intraperitoneal injection of 40 mg/kg of streptozotocin (STZ) for five consecutive days. IMODTM was administered at an effective dose of 20 mg/kg/day for 21 days. After 21 days of treatment, the pancreases of the animals were separated and homogenized. In the pancreas tissue, the level of lipid peroxidation as thiobarbituric acid reactive substances (TBARS), total antioxidant power as ferric reducing ability of pancreas (FRAP), myeloperoxidase (MPO), and the concentrations of interleukin-1 (IL-1) and tumour necrosis factor-a (TNF-α) were evaluated. Glucose changes were tested in the blood. Microscopic changes in the pancreas were followed by histological examinations. Results : No significant difference was found between IMODTM and diabetic control groups in blood glucose pattern. STZ-exposed mice showed a significant increase in pancreatic TBARS, MPO, IL-1, and TNF-α levels, along with a significant decrease in FRAP value. Co-administration of IMODTM significantly improved all the mentioned parameters disrupted by STZ administration except for blood glucose and histological changes. Conclusions : IMODTM could ameliorate oxidative and immunological distresses of type-1 immunogenic diabetes but could not normalize blood glucose. Further studies are recommended to clarify the effects of IMODTM on immunological factors to address whether this new agent could be applied in diabetes prevention or therapy.